2018
DOI: 10.1007/s00068-018-1005-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and treatment of femur fractures in adults with osteogenesis imperfecta: an analysis of an expert clinic of 216 patients

Abstract: Purpose Osteogenesis imperfecta (OI) is characterized by increased bone fragility and susceptibility for fractures. A few studies described and compared treatment modalities for femur fractures in children with OI. However, no cohort studies on adults with OI have been published. This study on adult OI patients aims to give insight into the incidence of femur fractures and non-unions and its best treatment options to avert non-union. Methods In this retrospective, descriptive study of the OI expert clinic in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Eleven patients had 15 femoral fractures (15.3%) and 4 non-unions (26.7%). Adults with type 4 OI tended to develop non-unions by conservative treatment for midshaft fractures similar to a previous study 18 . For all types of femoral fractures, the incidence was 651 fractures per 100,000 person-years annually.…”
Section: Discussionsupporting
confidence: 84%
“…Eleven patients had 15 femoral fractures (15.3%) and 4 non-unions (26.7%). Adults with type 4 OI tended to develop non-unions by conservative treatment for midshaft fractures similar to a previous study 18 . For all types of femoral fractures, the incidence was 651 fractures per 100,000 person-years annually.…”
Section: Discussionsupporting
confidence: 84%
“…Femoral shaft fractures are commonly observed in the clinic, 16,17 and the patient is at risk of deformity and dysfunction of the lower limb if they do not receive appropriate treatment. 18,19 Nonunion is a common complication of femoral shaft fracture, which may severely impact patient femoral function.…”
Section: Discussionmentioning
confidence: 99%
“…A study in children and adolescents with OI type I caused by COL1A1 haploinsufficiency mutations suggested that the rate of femur and tibia fractures was about 90 times higher than in their healthy peers . In adults with OI, it has been estimated that the incidence of femoral shaft fractures is about 35 times higher than in the general population …”
Section: Fracturesmentioning
confidence: 99%
“…(37) In adults with OI, it has been estimated that the incidence of femoral shaft fractures is about 35 times higher than in the general population. (38) Diaphyseal femur fractures are thus common in OI. Such fractures often occur after minimal trauma, are often transverse, are almost always complete, and are non-or minimally comminuted, thereby fulfilling four major criteria for establishing a diagnosis of atypical femur fractures, as defined for fractures that occur in the context of postmenopausal osteoporosis.…”
Section: Atypical Femur Fractures?mentioning
confidence: 99%